PENGEMBANGAN BUTIR SOAL HIGHER ORDER THINKING SKILL (HOTS) MATERI SISTEM KOORDINASI PADA SISWA SMA KELAS XI - Mustofa, Ali (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2021)
Conducting an assessment is one of the teacher's duties apart from compiling a learning program and implementing it in the classroom. The teacher must also be able to determine what can be obtained or achieved from the learning process that has been organized. The purpose of this study was to develop HOTS questions on the coordination system material and to test the quality of HOTS questions in the coordination system material for high school students in grade X. The subjects of this study consisted of 18 students who were selected purposively. Analysis of the items consisted of validity, reliability, difficulty level, differentiation, and trick effectiveness. The results of the analysis of the validity of the questions with a significant level of 5% for 18 students obtained 50 questions (92%) valid. The results of the reliability test of the items obtained the reliability index in the